Applying Facilitations in the Payment of Social Insurance Contributions as a Result of the So-called State of Social Insurance Finances - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu, 2013)
Applying facilitations in the payment of social insurance contributions is linked with, inter alia, the “state of social insurance finances”. The article was written in order to elaborate upon the term “state of social insurance finances”, as there is no literature on the subject. The author relates the term “state of social insurance finances” to such term as: state of public finances and public interest. It is indicated that the “state of social insurance finances” should be interpreted in the context of the finances of the largest and most significant fund of this type, the Social Insurance Fund. The author emphasizes that although remission of contribution payables has a tangible impact on social insurance finances, postponing payment or arrangement of payment in installments is of symbolic significance. The conclusions can lead to the assumption that the “state of social insurance finances” must be interpreted in a dynamic manner: depending on the types of facilitations and the financial situation of the Social Insurance Fund.